(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Surveying the status of characteristics of functional scale of the quality of life and determining the affected factors of female genital cancer patients at National Cancer Hospital from August 2020 to September 2021. Method: A cross-sectional descriptive study was performed on 700 female genital cancer patients using the EORTC QLQ-C30 questionare. Resuts: The highest mean score of physical function (79.0 ± 20.2); followed by perception (75.1 ± 24.4); emotional (73.0 ± 22.0), activity (64.1 ± 30.0) and social (63.4 ± 28.7) had the lowest. Factors affecting scores in functional domains include family/personal economics, cancer type, stage of disease, time of detection, comorbidities Conclusion: Measures are needed to improve functional scale of female genital cancer patients both during hospital treatment and after returning home.